PERAN PEMBIMBING KEMASYARAKATAN DALAM PROSES DIVERSI TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA PENCURIAN - Dommy Allen Driandhola (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Act Number 11 of 2012 on the Criminal Justice System Childrenmandates the SocialAdvisor is a functional officer of law enforcement who conducts community research,guidance, supervision, and mentoring to the Child inside and outside the criminal justiceprocess. A Civic adviser in the divertion of a child’s case is particularly important inproviding input and consideration to law enforcement officers in the form of CommunityResearch Report.